First-principles calculations of the optical response of single-layer and bilayer armchair graphene nanoribbons - Ge, Yijun; Fisher, Timothy S. (Frontiers in Nanotechnology, 2022)
Electronic and optical properties of single-layer and bilayer armchair graphene nanoribbons are investigated using a first-principles method. Increased nanoribbon width reduces the band gap and causes a red shift in photon absorption energy. The 3n+2 family of nanoribbons has the smallest band gaps and lowest onset photon absorption energy among the three families considered due to high π-conjugation indicated by exciton wavefunctions. We also compare the bilayer α and β alignments of armchair graphene nanoribbons with their single-layer counterparts. The extra layer of graphene reduces the band gap and onset photon absorption energy, and the difference between the α alignment and the single-layer configuration is more significant than that of the β alignment and the single layer. Our calculations indicate that the optical properties of graphene nanoribbons depend on the details of atomic structures, including nanoribbon width, edge alignment and number of layers. These characteristics are expected to be important in the design of optoelectronic devices.